Petroleum rock mechanics : drilling operations and well design - Aadnøy, Bernt Sigve; Looyeh, Reza (Gulf Professional Publishing, an imprint of Elsevier, 2019)
Petroleum Rock Mechanics: Drilling Operations and Well Design, Second Edition, keeps petroleum and drilling engineers centrally focused on the basic fundamentals surrounding geomechanics, while also keeping them up-to-speed on the latest issues and practical problems. Updated with new chapters on operations surrounding shale oil, shale gas, and hydraulic fracturing, and with new sections on in-situ stress, drilling design of optimal mud weight, and wellbore instability analysis, this book is an ideal resource. By creating a link between theory with practical problems, this updated edition continues to provide the most recent research and fundamentals critical to today's drilling operations. Key Features: Helps readers grasp the techniques needed to analyze and solve drilling challenges, in particular wellbore instability analysis; Teaches rock mechanic fundamentals and presents new concepts surrounding sand production and hydraulic fracturing operations; Includes new case studies and sample problems to practice. -- Provided by publisher.
Keywords: Petroleum -- Geology.; Rock mechanics.; elektronické knihy; electronic books